Potential use of coconut husk-based magnetic sorbent for defoaming application - Terry Lo, Felicia; Lim, Soh Fong; David Chua, Sing Ngie; Lau, Kok Keong; Chin, Sim Yee (Elsevier B.V., 2023)
Absorption process is the most common method that is being applied to sweeten sour gas in the oil and gas industry. However, this process does have several consequences which will trigger the foam formation of foam that will reduce the mass transfer efficiency and absorption capacity as well as amine solutions carryover to the downstream processes. The removal of undesired contaminants in activated methyldiethanolamine (MDEA) was conducted by utilizing magnetic activated carbon (MAC). In this work, MAC was synthesized from coconut husk through chemical activation and co-precipitation methods. The performance of this material as an adsorbent was evaluated based on the foaming behaviour of activated MDEA solvent after being contacted with MAC at different duration and varying amounts. Nitrogen gas was introduced into the solvent through a gas diffuser to create foam. Based on the results, the foam volume generated by activated MDEA solvent was identified to decrease with the increase in both MAC contact time and amount. The highest removal efficiency by MAC was identified to be at 1 h contact time between MAC and activated MDEA solvent where the foam breaking time was reduced to 10–30 min. Meanwhile, the addition of 50 % MAC into the solvent was able to further decrease the foam breaking time to 5–10 min. The characteristics of the prepared MAC were evaluated through various instrumental analyses. This study shows that the MAC synthesized from coconut husk has a good potential as an adsorbent in removing the contaminants in activated MDEA solvent to reduce foam formation.